Effect of integrated plant nutrient system (IPNS) on the soil biological regimes in red loam soil - Neethu R Sathyan (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2013)
The research entitled "Effect of integrated plant nutrient system (IPNS) on the soil biological regimes in red loam' soil" was a study undertaken in the Dept. of Soil Science and Agrl. Chemistry during the period from March 2012 to June 2012. The objective of the study was to assess the conjugal effect of manures and chemical fertilizers on dynamics of major agriculturally significant soil enzymes, available nutrient status of the soil, its relation with the activities of major soil enzymes, soil micro flora, yield and yield attributes of the test crop and computation of Biological Fertility Index through Enzyme Activity Number. Field experiment using bhindi as test crop consisted of 15 treatments. The treatments were laid out in RBD with three replications. The treatments were T1_ Package of practice recommendation (KAU), T2 _ N (25 %) as neem cake enriched vermicompost + N (75%), P & K, T3 _ N (25 %) as Azospirillum enriched vermicompost + N (75%), P & K, T4 _ P (25 %) as PSB enriched vermicompost + P (75%), N & K, T5- NPK (25 %) as PGPR mix-1 enriched vermicompost + N, P & K (75%), T6- N (50%) as Neem cake enriched vermicompost+ N (50%), P & K, T7- N (50%) as Azospirillum enriched vermicompost + N (50%), P & K, Ts- P (50 %) as PSB enriched vermicompost + P (50%), N & K, T9 _ NPK (50 %) as PGPR mix-1 enriched vermicompost + N, P & K (50%), TlO. N (75 %) as Neem cake enriched vermicompost + N (25%),P & K, T11_ N (75 %) as Azospirillum enriched vermicompost + N (25%), P & K , T12- P (75%) as PSB enriched vermicompost + P (25%), N & K, TJ3_,N, P, K, (75 %) as PGPR mix-1 enriched vermicompost + N, P & K (25%), T14- N, P, K alone as inorganics, T 15- Absolute control